Research progress on ferroptosis in colorectal cancer - Li, Yuan; Bi, Yao; Li, Wenjing; Piao, Yingshi; Piao, Junjie; Wang, Tong; Ren, Xiangshan (Frontiers in Immunology, 2024)
Ferroptosis is a new form of cell death that differs from traditional forms of death. It is ferroptosis-dependent lipid peroxidation death. Colorectal cancer(CRC) is the most common tumor in the gastrointestinal tract with a long occultation period and a poor five-year prognosis. Exploring effective systemic treatments for CRC remains a great challenge worldwide. Numerous studies have demonstrated that ferroptosis can participate in the biological malignant process of various tumor, including CRC, so understanding the role and regulatory mechanisms of ferroptosis in CRC plays a crucial role in the treatment of CRC. In this paper, we reviews the mechanisms of ferroptosis in CRC, the associated regulatory factors and their interactions with various immune cells in the immune microenvironment. In addition, targeting ferroptosis has emerged as an encouraging strategy for CRC treatment. Finally, to inform subsequent research and clinical diagnosis and treatment, we review therapeutic approaches to CRC radiotherapy, immunotherapy, and herbal therapy targeting ferroptosis.